Source-specific oxidative potential and health risks of PM2.5-bound toxic elements in Xiamen Port: Insights into ship emission contributions - Si-Min Zhao; Qi-Yu Miao; Jia-Min Li; Xin-Ye Wu; Bing-Qi Jiang; Li-Xiong He; Yi-Jing Liu; Zhi Huang; Chung-Shin Yuan; Shui-Ping Wu (Atmospheric Pollution Research, 2026)

Hexamermis jengi n. sp. (Nematoda: Mermithidae) parasitizing grasshoppers and the invasive fall armyworm in Taiwan and Thailand - Ping-Chieh Lee; Ace Kevin S. Amarga; Wen-Hua Chen; Li-Hsin Wu; Chuan-Kai Ho; Chun-I Chiu; Ming-Chung Chiu (Journal of Invertebrate Pathology, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Reconceptualizing chorioamnionitis as an immune-mediated inflammatory disorder at the maternal–fetal interface - Tzu-Ming Wang; Chung-Min Shen; Shih-Chang Lin; Wu-Shiun Hsieh; Yi-Li Hung; Jiun-Wen Guo (Inflammation Research, 2026)

Direct conversion of N2 to nitrogen-containing organics via a plasma-electrochemical cascade reaction approaching 100% yield - Wenjie Wu; Ao Qin; Cairong Wang; Ta Thi Thuy Nga; Leitao Xu; Yandong Wu; Ruiqi Wang; Zhongcheng Xia; Zhonghuan Zhu; Yulu Yang; Chuang Fu; Chung-Li Dong; et al. (Science Bulletin, 2026)

Self-catalyzed NiFe foam anode fabricated via tape-casting for oxygen evolution reaction in anion exchange membrane water electrolysis - Li-Da Chiu; Calvin Leo Putra; Shuo-En Yu; I-Chung Cheng; I-Chih Ni; Chih-I Wu; I-Chun Cheng; Jian-Zhang Chen (Fuel, 2026)

Imiquimod-induced colitis: A novel ROS/ERK-driven model of intestinal inflammation and barrier dysfunction - Kuang-Ting Liu; Shu-Hao Chang; Kuan-Chen Wu; Zheng-Yi Li; Mao-Chia Chang; Yen-Chu Huang; Mu-Chi Chung; Shih-Chung Wang; Yi-Ju Chen; Jeng-Jer Shieh (Chemico-Biological Interactions, 2026)

Anti-inflammatory constituents from Murraya paniculata var. omphalocarpa - Kun-Ching Cheng; Chia-Hung Wu; Hao-Ze Li; Tsong-Long Hwang; Ping-Chung Kuo; Tian-Shung Wu (Phytochemistry Letters, 2026)

Potential role of oocyte-intrinsic fatty acid synthesis in ovarian development of the bigfin reef squid Sepioteuthis lessoniana - Hau-Wen Li; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2026)
In most animals, excess dietary energy is stored as lipids in specialized tissues, such as the liver in vertebrates or the hepatopancreas and fat body in invertebrates, which function as energy reservoirs for reproduction. In cephalopods, however, dietary energy is rapidly mobilized from the digestive gland for growth rather than stored for reproduction. How excess energy is allocated for reproduction activity in cephalopods remains largely unclear. Lipogenesis is initiated by acetyl-CoA carboxylase (ACC), which converts acetyl-CoA derived from dietary carbon sources into malonyl-CoA; subsequent synthesis of saturated fatty acids is catalyzed by fatty acid synthase (FAS). Using the bigfin reef squid as a model, we investigate the role of fas in female development. fas mRNA was highly expressed in ovaries but weak in other tissues, including the lipid-rich digestive gland. fas showed female-biased expression in gonads, with level highest in juvenile ovaries and progressively decreasing to their lowest in mature ovaries. Expression was also high in primary and multiple follicular oocytes but declined in later stages. In situ hybridization and immunohistochemistry confirmed fas mRNA and protein localization in oocytes, particularly in primary and multiple follicular oocytes. In vitro ovarian culture further showed that inhibiting FAS activity enhanced somatic cell proliferation. Together, these findings suggest that squid ovary is a primary site of fatty acid synthesis, supporting early oocyte growth and membrane biogenesis in the absence of dedicated lipid storage tissues. The decline of FAS activity during oogenesis, and the associated reproduction in fatty acid synthesis, may act as a regulatory signal to promote somatic cell proliferation.

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

Gene expressions in newborns and the association with prenatal exposure to phthalate plasticizers – The Taiwan Maternal and Infant Cohort Study (TMICS) - Yi-Ju Wu; Hui-Ju Wen; Chung-Hsing Chen; Shin-Fen Tsai; Shih Sheng Jiang; Shu-Li Wang (Journal of Hazardous Materials, 2025)

Streptococcus atopica sp. nov., Isolated from the Feces of a Toddler with Atopic Dermatitis - Chin-Kan Chan; Hui-Shan Wu; Li-Jyun Tsai; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yi-Sheng Chen (Current Microbiology, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Effects of pyrolysis temperature on the biochar-derived horse manure: Physicochemical characteristics and catalytic activation of peroxymonosulfate activation toward sulfamethoxazole degradation in aqueous solution - Li-Min Chiang; Thanh-Binh Nguyen; Chiu-Wen Chen; Cheng-Di Dong; Chung-Hsin Wu (Journal of Water Process Engineering, 2025)

Sensitive detection of boron-containing drug delanzomib by a luminescence probe in health-related samples - Shaozhen Jing; Xiaolei Wu; Xueliang Wang; Daniel Shiu-Hin Chan; Tsun-Yin Li; Chun-Yuen Wong; Chung-Hang Leung; Wanhe Wang; Jing Wang (Analytica Chimica Acta, 2025)

Ash thermomechanical properties and combustion characteristics during Co-combustion of anthracite and biomass for CFB combustors - Shangkun Quan; Yijie Zeng; Yukun Wu; Ryang-Gyoon Kim; Zhouhang Li; Yong Han; Junjie Li; Chung-hwan Jeon; Xing Zhu; Hua Wang; Dongfang Li (Biomass and Bioenergy, 2025)

Analysis of profuse winter rainfall over Northern Taiwan and weather-type association - Jen-Ping Chen; Pei-Chun Tsai; Li-Ru Chen; Chung-Kai Wu; Emmanuel Fontaine (Atmospheric Research, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Enhanced simulated sunlight photolysis of antibiotics on soil surfaces by biochar: Effects and mechanisms - Yuying Wu; Dengmiao Cheng; Jisen Xiong; Shaoyu Tang; Jonathan Woon Chung Wong; Zhaojun Li (Journal of Environmental Management, 2025)

Co-existence of airborne SARS-CoV-2 infection and non-infection in three connected zones of a restaurant - Wei Jia; Qun Wang; David Christopher Lung; Pak-To Chan; Peihua Wang; Edwin Chung-Hin Dung; Tiffany Didik; Garnet Kwan-Yue Choi; Herman Tse; Yijie Wu; Te Miao; Wenzhao Chen; et al. (Journal of Hazardous Materials, 2024)

Epidemiology of human metapneumovirus in Taiwan from 2013 to 2023 - Su-Lin Yang; Tai-Yuan Chiu; Kun-Lin Tsai; Chung-Hao Li; Jyh-Yuan Yang; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

An acridone based fluorescent dye for lipid droplet tracking and cancer diagnosis - Dat Thanh Dinh; Chia-Ying Li; Min-Wei Wu; Chia-Feng Hsieh; Xuan-Yu Chen; Cheng-Chung Chang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Air pollution mixture associated with oxidative stress exacerbation and symptoms deterioration in allergic rhinitis patients: Evidence from a panel study - Jinhui Li; Haisheng Wu; Weiwei Xing; Xin Li; Zheshen Han; Renyue Ji; Zhengyi Deng; Minji Jung; Shengzhi Sun; Benjamin I. Chung; Andres Cardenas; Marvin E. Langston (Science of The Total Environment, 2024)

An emerging pathogen found in farm-cultured fourfinger threadfin (Eleutheronema tetradactylum), Edwardsiella piscicida, its genetic profile, virulent genes, and pathogenicity - Li-Wu Cheng; Hsien-Chung Lee; Qiong-Yi Huang; Wen-Rou Huang; Pei-Chi Wang; Shih-Chu Chen (Aquaculture, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Exposure to particulate matter may affect semen quality via trace metals: Evidence from a retrospective cohort study on fertile males - Yuting Cheng; Jiaqi Zhu; Qiuqin Tang; Jing Wang; Jialin Feng; Yijie Zhou; Jinhui Li; Feng Pan; Xiumei Han; Chuncheng Lu; Xinru Wang; Marvin E. Langston; et al. (Chemosphere, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Dose-response formation of N7-(3-benzo[1,3]dioxol-5-yl-2-hydroxypropyl)guanine in liver and urine correlates with micronucleated reticulocyte frequencies in mice administered safrole oxide - Kuen-Yuh Wu; Yu-Tzu Wei; Yu-Syuan Luo; Li-Chin Shen; Bao-Suei Chang; Ya-Yin Chen; Yan-Chi Huang; Hui-Fen Huang; Wen-Sheng Chung; Su-Yin Chiang (Food and Chemical Toxicology, 2023)

Utilizing Numerical Models and GIS to Enhance Information Management for Oil Spill Emergency Response and Resource Allocation in the Taiwan Waters - Chi-Min Chiu; Laurence Zsu-Hsin Chuang; Wei-Liang Chuang; Li-Chung Wu; Ching-Jer Huang; Yinglong Joseph Zhang (Journal of Marine Science and Engineering, 2023)
This study aims to establish a comprehensive workflow for developing emergency response plans for both actual and scenario oil spill incidents in the Taiwan waters while addressing the resource allocation for oil spill containment as well. This workflow comprises two vital components. The first component involves the integration of numerical tools and observational data, which includes the incorporation of wind data from sources such as the National Centers for Environmental Prediction (NCEP) or meteorological stations. Additionally, it incorporates ocean current data simulated by the semi-implicit cross-scale hydroscience integrated system model (SCHISM) into the general NOAA operational modeling environment (GNOME) model, which is a new approach for this purpose. In order to assess the efficacy of this component, two distinct case studies were conducted. The first case study focused on an incident in a northern coastal area of Taiwan under open sea conditions, whereas the second case study examined an incident within a major commercial harbor in central Taiwan. The second component of this workflow involves creating oil risk maps by integrating the results from the first component with specific geographical factors into Google Earth. These oil risk maps serve multiple purposes. They offer real-time information to emergency response commanders regarding oil spill hazard prediction, and they also enable the effective development of emergency response strategies and disposal plans for potential oil spill incidents. This is achieved by generating risk maps for various scenarios using the approach outlined in the first component. Additionally, these maps assist in the assessment and planning of resource allocation for oil containment.

Different Burial-Cooling History of Triassic Strata between the Western Weibei Uplift and the Northwestern Weihe Basin in Northwest China - Qiang Yu; Zhanli Ren; Rongxi Li; Chung Ling; Tao Ni; Wanshan Lei; Baojiang Wang; Xiaoli Wu; Xiaoli Qin; Xianghe Lei (Journal of Earth Science, 2023)

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Electrochemical etching induced high-valence cobalt with defects site for boosting electrochemical water splitting - Hongmei Gao; Jiaqi Liu; Zijin Zhang; Yuxuan Lu; Ru Chen; Yu-Cheng Huang; Chao Xie; Mengyi Qiu; Tianyu Wu; Jinbo Wang; Yubin Jiang; Chung-Li Dong; et al. (Chemical Engineering Journal, 2023)

Evaluation of wetting measures and capture efficiencies of fugitive dust emitted from a limestone pile: Experiments and artificial neural network - Po-Hsuan Yen; Justus Kavita Mutuku; Chung-Shin Yuan; Wei-Hsiang Chen; Chih-Cheng Wu; Chien-Sen Li (Process Safety and Environmental Protection, 2023)

Entomopathogenic fungi-mediated biological control of the red palm weevil Rhynchophorus ferrugineus - Tzu-Hao Yang; Li-Hsin Wu; Chung-Ta Liao; Dongwei Li; Tae Young Shin; Jae Su Kim; Yu-Shin Nai (Journal of Asia-Pacific Entomology, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Peng-Wei Tseng; Hau-Wen Li; Chih Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana , are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Design and construction of an O-Au-O coordination environment in Au single atom-doped Ti4+ defected TiO2 for an enhanced oxidative ability of lattice oxygen for Hg0 oxidation - Zhilei Guo; Guohua Jing; Sara A. Tolba; Chung-shin Yuan; Yu-Hua Li; Xiaowei Zhang; Zhiwei Huang; Huawang Zhao; Xiaomin Wu; Huazhen Shen; Wenjie Xia (Chemical Engineering Journal, 2023)

Bragg-region recognition of high-frequency radar spectra based on deep learning and image fusion processing - Laurence Zsu-Hsin Chuang; Yu-Ru Chen; Yu-Jen Chung; Li-Chung Wu; Tsung-Mo Tien (International Journal of Remote Sensing, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Blocking Hepatoma-Derived Growth Factor Attenuates Vasospasm and Neuron Cell Apoptosis in Rats Subjected to Subarachnoid Hemorrhage - Chia-Li Chung; Chieh-Hsin Wu; Yu-Hua Huang; Shu-Chuan Wu; Chee-Yin Chai; Hung-Pei Tsai; Aij-Lie Kwan (Translational Stroke Research, 2022)
Subarachnoid hemorrhage (SAH) is an important subcategory of stroke due to its unacceptably high mortality rate as well as the severe complications it causes, such as cerebral vasospasm, neurological deficits, and cardiopulmonary abnormality. Hepatoma-derived growth factor (HDGF) is a growth factor related to normal development and is involved in liver development and regeneration. This study explored the relationship between SAH and HDGF. Sixty rats were divided into five groups (n = 12/group): (A) control group; (B) rHDGF ab only group [normal animals treated with 50 µM recombinant HDGF antibodies (rHDGF ab)]; (C) SAH group; (D) SAH + pre-rHDGF ab group (SAH animals pre-treated with 50 µM rHDGF ab into the subarachnoid space within 24 h before SAH); and (E) SAH + post-rHDGF ab group (SAH animals post-treated with 50 µM rHDGF ab into the subarachnoid space within 24 h after SAH). At 48 h after SAH, serum and cerebrospinal fluid (CSF) samples were collected to measure the levels of pro-inflammatory factors by ELISA, and rat cortex tissues were used to measure protein levels by western blot analysis. Immunofluorescence staining for Iba-1, GFAP, TUNEL, and NeuN was detected proliferation of microglia and astrocyte and apoptosis of neuron cells. Neurological outcome was assessed by ambulation and placing/stepping reflex responses. Morphology assay showed that pre-treatment and post-treatment with rHDGF ab attenuated vasospasm after SAH. SAH up-regulated the levels of TNF-α, IL-1β, and IL-6 in both the CSF and serum samples, and both pre- and post-treatment with rHDGF ab inhibited the up-regulation of these pro-inflammatory factors, except for the serum IL-6 levels. Western blot analysis demonstrated that SAH up-regulated pro-BDNF and NFκB protein levels, and both pre- and post-treatment with rHDGF ab significantly reduced the up-regulation. The result from immunofluorescence staining showed that SAH induced proliferation of microglia and astrocyte and apoptosis of neuron cells. Both pre- and post-treatment with rHDGF ab significantly attenuated proliferation of microglia and astrocyte and inhibited apoptosis of neuron cells. Furthermore, treatment with rHDGF ab significantly improved neurological outcome. Blocking HDGF attenuates neuron cell apoptosis and vasospasm through inhibiting inflammation in brain tissue at early phase after SAH.

Size distributions and dry deposition fluxes of water-soluble inorganic nitrogen in atmospheric aerosols in Xiamen Bay, China - Shui-Ping Wu; Xiang Li; Yang Gao; Mei-Jun Cai; Chao Xu; James J. Schwab; Chung-Shin Yuan (Journal of Atmospheric Chemistry, 2022)

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Size distributions and health risks of particle-bound toxic elements in the southeast coastland of China - Shui-Ping Wu; Xiang Li; Mei-Jun Cai; Yang Gao; Chao Xu; James J. Schwab; Chung-Shin Yuan (Environmental Science and Pollution Research, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Characterization of teaghrelin-like compounds from tea cultivars - Ping-Chung Kuo; Yue-Chiun Li; Ruo-Hsuan Wu; Jason T. C. Tzen (Natural Product Research, 2021)

Natural products development under epigenetic modulation in fungi - Chi-Ying Li; Yu-Ming Chung; Yang-Chang Wu; Attila Hunyadi; Clay C. C. Wang; Fang-Rong Chang (Phytochemistry Reviews, 2020)

Relationships among cigarette smoking, urinary biomarkers, and urothelial carcinoma risk: a case-control study - Chi-Jung Chung; Hui-Tsung Hsu; Chao-Hsiang Chang; Sheng-Wei Li; Chiu-Shong Liu; Mu-Chi Chung; Guo-Wei Wu; Wei-Ting Jung; Yen-Jung Kuo; Hui-Ling Lee (Environmental Science and Pollution Research, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Expression of long pentraxin 3 in human nasal mucosa fibroblasts, tissues, and secretions of chronic rhinosinusitis without nasal polyps - Yih-Jeng Tsai; Chung-Yu Hao; Chih-Li Chen; Pi-Hui Wu; Wen-Bin Wu (Journal of Molecular Medicine, 2020)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Identification of sugar response complex in the metallothionein OsMT2b gene promoter for enhancement of foreign protein production in transgenic rice - Chia-Yu Chang; Kuo-Wei Lee; Chung-Shen Wu; Yu-Hsing Huang; Ho-Chun Chang; Chien-Lung Chen; Chen-Tung Li; Min-Jeng Li; Chung-Fu Chang; Peng-Wen Chen (Plant Cell Reports, 2019)

Ginsenoside Rg1 Prevents Chemotherapy-Induced Cognitive Impairment: Associations with Microglia-Mediated Cytokines, Neuroinflammation, and Neuroplasticity - Dong-Dong Shi; Yu-Hua Huang; Cora Sau Wan Lai; Celia M. Dong; Leon C. Ho; Xiao-Yang Li; Ed X. Wu; Qi Li; Xiao-Min Wang; Yong-Jun Chen; Sookja Kim Chung; Zhang-Jin Zhang (Molecular Neurobiology, 2019)

Expression Profiling of Notch Signalling Pathway and Gamma-Secretase Activity in the Brain of Ts1Cje Mouse Model of Down Syndrome - Hadri Hadi Yusof; Han-Chung Lee; Eryse Amira Seth; Xiangzhong Wu; Chelsee A. Hewitt; Hamish S Scott; Pike-See Cheah; Yue-Ming Li; De-Ming Chau; King-Hwa Ling (Journal of Molecular Neuroscience, 2019)

Chemotherapy-Induced Cognitive Impairment Is Associated with Cytokine Dysregulation and Disruptions in Neuroplasticity - Dong-Dong Shi; Yu-Hua Huang; Cora Sau Wan Lai; Celia M. Dong; Leon C. Ho; Ed X. Wu; Qi Li; Xiao-Min Wang; Sookja Kim Chung; Pak Chung Sham; Zhang-Jin Zhang (Molecular Neurobiology, 2019)

Chemical characteristics, source apportionment, and regional transport of marine fine particles toward offshore islands near the coastline of northwestern Taiwan Strait - Cheng-Chih Chang; Chung-shin Yuan; Tsung-Chang Li; Yen-Lung Su; Chuan Tong; Shui-Ping Wu (Environmental Science and Pollution Research, 2018)

Composition of harvested seeds and seed selection by the invasive tropical fire ant, Solenopsis geminata (Hymenoptera: Formicidae) in Taiwan - Li-Chuan Lai; Ming-Chung Chiu; Chih-Wei Tsai; Wen-Jer Wu (Arthropod-Plant Interactions, 2018)

Extremely low genetic diversity across mangrove taxa reflects past sea level changes and hints at poor future responses - Zixiao Guo; Xinnian Li; Ziwen He; Yuchen Yang; Wenqing Wang; Cairong Zhong; Anthony J. Greenberg; Chung‐I Wu; Norman C. Duke; Suhua Shi (Global Change Biology, 2018)
The projected increases in sea levels are expected to affect coastal ecosystems. Tropical communities, anchored by mangrove trees and having experienced frequent past sea level changes, appear to be vibrant at present. However, any optimism about the resilience of these ecosystems is premature because the impact of past climate events may not be reflected in the current abundance. To assess the impact of historical sea level changes, we conducted an extensive genetic diversity survey on the Indo‐Malayan coast, a hotspot with a large global mangrove distribution. A survey of 26 populations in six species reveals extremely low genome‐wide nucleotide diversity and hence very small effective population sizes ( N e ) in all populations. Whole‐genome sequencing of three mangrove species further shows the decline in N e to be strongly associated with the speed of past changes in sea level. We also used a recent series of flooding events in Yalong Bay, southern China, to test the robustness of mangroves to sea level changes in relation to their genetic diversity. The events resulted in the death of half of the mangrove trees in this area. Significantly, less genetically diverse mangrove species suffered much greater destruction. The dieback was accompanied by a drastic reduction in local invertebrate biodiversity. We thus predict that tropical coastal communities will be seriously endangered as the global sea level rises. Well‐planned coastal development near mangrove forests will be essential to avert this crisis.

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Biogeographical diversification of mainland Asian Dendrobium (Orchidaceae) and its implications for the historical dynamics of evergreen broad‐leaved forests - Xiao‐Guo Xiang; Xiang‐Cheng Mi; Hai‐Lang Zhou; Jian‐Wu Li; Shih‐Wen Chung; De‐Zhu Li; Wei‐Chang Huang; Wei‐Tao Jin; Zhen‐Yu Li; Lu‐Qi Huang; Xiao‐Hua Jin (Journal of Biogeography, 2016)
Aim Evergreen broad‐leaved forests ( EBLF s) occupy most tropical and subtropical regions of mainland Asia and exhibit high species diversity, productivity and richness. Understanding the historical dynamics of EBLF s is important for biodiversity conservation and regional carbon storage and cycling under global climate change. However, little is known about the historical dynamics of EBLF s in mainland Asia. Dendrobium , an epiphytic orchid genus found in EBLF s, was used to gain new insights of the historical establishment and extension of EBLF s in mainland Asia. Location Mainland Asia. Methods We sampled c . 80% of the currently recognized species of Dendrobium found in mainland Asia. A phylogeny was generated using maximum parsimony, maximum likelihood and Bayesian inference methods. A calibrated chronogram was obtained using a Bayesian relaxed‐clock model approach. Biogeographical scenarios were investigated using the statistical dispersal–vicariance analysis and dispersal–extinction–cladogenesis methods. Ancestral states were constructed by mesquite and bayestraits , and diversification of Dendrobium was investigated by APE and LASER packages. Results Our results indicate that Asian Dendrobium was present on mainland Asia since the Oligocene, after which this genus diversified in this region and dispersed into higher elevations. The ancestral habit of Dendrobium was epiphytic and terrestrial and lithophytic habits each have multiple, recently independent origins. Main conclusions Our results support the hypothesis that EBLF s have been established in mainland Asia at least since the Oligocene and further suggest that the EBLF s of mainland Asia expanded into higher elevations prior to the late Cenozoic. The diversification of Asian Dendrobium coincided with a warmer climate during the late Oligocene and middle Miocene and the expansion of key groups (including Fagaceae, Lauraceae, Magnoliaceae and Theaceae) of EBLF s during the early Cenozoic.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Sesamol suppresses the inflammatory response by inhibiting NF-κB/MAPK activation and upregulating AMP kinase signaling in RAW 264.7 macrophages - Xin-Ling Wu; Chian-Jiun Liou; Zih-Ying Li; Xuan-Yu Lai; Li-Wen Fang; Wen-Chung Huang (Inflammation Research, 2015)

A single-repeat MYB transcription repressor, MYBH, participates in regulation of leaf senescence in Arabidopsis - Chun-Kai Huang; Pei-Ching Lo; Li-Fen Huang; Shaw-Jye Wu; Ching-Hui Yeh; Chung-An Lu (Plant Molecular Biology, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Double homeobox gene, Duxbl, promotes myoblast proliferation and abolishes myoblast differentiation by blocking MyoD transactivation - Shey-Lin Wu; Guo-Zili Li; Chin-Yi Chou; Ming-Shiun Tsai; Yi-Pei Chen; Chung-Jung Li; Gan-Guang Liou; Wen-Wei Chang; Shen-Liang Chen; Sue-Hong Wang (Cell and Tissue Research, 2014)

Divergence of the expression and subcellular localization of CCR4-associated factor 1 (CAF1) deadenylase proteins in Oryza sativa - Wei-Lun Chou; Li-Fen Huang; Jhen-Cheng Fang; Ching-Hui Yeh; Chwan-Yang Hong; Shaw-Jye Wu; Chung-An Lu (Plant Molecular Biology, 2014)

The promoter and the 5′-untranslated region of rice metallothionein OsMT2b gene are capable of directing high-level gene expression in germinated rice embryos - Chung-Shen Wu; Dai-Yin Chen; Chung-Fu Chang; Min-Jeng Li; Kuei-Yu Hung; Liang-Jwu Chen; Peng-Wen Chen (Plant Cell Reports, 2014)

Thrombin Mediates Migration of Rat Brain Astrocytes via PLC, Ca2+, CaMKII, PKCα, and AP-1-Dependent Matrix Metalloproteinase-9 Expression - Chih-Chung Lin; I-Ta Lee; Wen-Bin Wu; Chiung-Ju Liu; Hsi-Lung Hsieh; Li-Der Hsiao; Chien-Chung Yang; Chuen-Mao Yang (Molecular Neurobiology, 2013)

Palladium-catalyzed regioselective synthesis of 2(2 $$^{′ }$$ ′ -biphenyl)benzimidazoles through C–H activation - Li-Hsun Chen; Tz-Yi Wu; Vijaykumar Paike; Chung-Ming Sun (Molecular Diversity, 2013)

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Ocean remotely sensed image analysis using two-dimensional continuous wavelet transforms - Li-Chung Wu; Laurence Zsu-Hsin Chuang; Dong-Jiing Doong; Chia Chuen Kao (International Journal of Remote Sensing, 2011)

Changes of Curdlan Biosynthesis and Nitrogenous Compounds Utilization Characterized in ntrC Mutant of Agrobacterium sp. ATCC 31749 - Li-Jun Yu; Jian-Rong Wu; Zhi-Yong Zheng; Xiao-Bei Zhan; Chi Chung Lin (Current Microbiology, 2011)

Quantification of non-homogeneity from ocean remote-sensing images using two-dimensional continuous wavelet transforms - Li-Chung Wu; Laurence Zsu-Hsin Chuang; Dong-Jiing Doong; Chia Chuen Kao (International Journal of Remote Sensing, 2011)

Secondary metabolites from the red mould rice of Monascus purpureus BCRC 38113 - Ming-Jen Cheng; Ming-Der Wu; Ih-Sheng Chen; Chung-Yi Chen; Wen-Li Lo; Gwo-Fang Yuan (Natural Product Research, 2010)

Inactivation of Staphylococcus aureus and Escherichia coli in Water Using Photocatalysis with Fixed TiO2 - Chih-Yu Chen; Li-Chun Wu; Hsuan-Yu Chen; Ying-Chien Chung (Water, Air, & Soil Pollution, 2010)

Prospective variants screening of connexin genes in children with hearing impairment: genotype/phenotype correlation - Jiann-Jou Yang; Wen-Hung Wang; Yen-Chun Lin; Hsu-Huei Weng; Jen-Tsung Yang; Chung-Feng Hwang; Che-Min Wu; Shuan-Yow Li (Human Genetics, 2010)

Biochemical characterization of the small ubiquitin-like modifiers of Chlamydomonas reinhardtii - Yung-Cheng Shin; Bang-Yu Liu; Jia-Yun Tsai; Jiunn-Tzong Wu; Li-Kwan Chang; Shih-Chung Chang (Planta, 2010)

Evaluation of the bioactivities of extracts of endophytes isolated from Taiwanese herbal plants - Pei-Wen Hsieh; Li-Chi Hsu; Chern-Hsiung Lai; Chin-Chung Wu; Tsong-Long Hwang; Yin-Ku Lin; Yang-Chang Wu (World Journal of Microbiology and Biotechnology, 2009)

Nonlinear influences on ocean waves observed by X-band radar - Li-Chung Wu; Dong-Jiing Doong; Beng-Chun Lee; Laurence Zsu-Hsin Chuang; Chia Chuen Kao (Marine Geophysical Research, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Seasonal variations of wind and waves over Taiwan waters - Beng-Chun Lee; Li-Chung Wu; Dong-Jiing Doong; Chia Chuen Kao (Marine Geophysical Research, 2007)

Effects of rosiglitazone on native low-density-lipoprotein-induced respiratory burst in circulating monocytes and on the leukocyte–endothelial interaction in cholesterol-fed rats - Long Sheng Lu; Li Man Hung; Chang Hui Liao; Chau Chung Wu; Ming Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Expression and Export of Pseudomonas putida NTU-8 Creatinase by Escherichia coli Using the Chitinase Signal Sequence of Aeromonas hydrophila - Ming Chuan Hong; Jinq Chyi Chang; Mei Li Wu; Ming Chung Chang (Biochemical Genetics, 1998)

Cell density-dependent proliferation of the murine bone marrow-derived stromal cell lines - Li-Chung Huang; JH David Wu (Biotechnology Letters, 1997)